Towards the mapping of port labour systems and conflicts across Europe: a literature review. (1st April 2019) - Bottalico, Andrea
Abstract : This article presents a literature review on labour dynamics in European ports. The aim is to provide a detailed and critical appraisal of the recent academic literature on port labour studies, in order to develop a comprehensive mapping of the variety of port labour regimes and conflicts in Europe with the ultimate aim of revealing the changing profile of labour requirements as a consequence of the structural transformations in the overall logistics chain. The review mainly considers the literature published during the period 2000-2017. Since ports have been explored by means of different theoretical approaches, paradigms and perspectives, the study aimed to foster a multidisciplinary approach between some streams and to consolidate them wherever possible. In the first part of the article, the main definitions, ideas and concepts developed in the literature by scholars on seaport research and port studies are reviewed and analysed. The second part discusses the literature on port geography and the third part addresses port labour dynamics in particular. The conclusions draw from the perspective of the maritime-logistics chain to analyse the variety of port labour systems and summarise the literature reviewed, stressing the need for further studies.